Optimasi Proses Gasifikasi Menggunakan Logika Fuzzy Mamdani - Bagus Fatkhurrozi; Sapto Nisworo; Sumardi Sumardi (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2022)
This study aims to test the performance of fuzzy logic in the gasification process. Gasification is the process of converting solids into flammable gases. The gas produced becomes an alternative energy source, namely the Waste Power Plant (PLTSa). The research applies Mamdani's Fuzzy logic. Fuzzy logic was created using Matlab R2018b software. The results obtained indicate that the Mean Absolute Error (MAE) output of H2 on fuzzy logic training data is 6.57. The test results for CO fuzzy output MAE value of 1.12. The test results on CO2 MAE fuzzy are 1.18. In the CH4 test, the MAE fuzzy output is 0,84.